ANALISIS PRODUKTIVITAS TENAGA KERJA SEKTOR PERTANIAN PADA MASA PANDEMI COVID-19 DI PROVINSI RIAU - Dian Chintya Dewi; Sufiyan Ardi; Sisca Vaulina (Fakultas Pertanian, Universitas Riau, 2022)
The role agricultural sector as a contributor Gross Regional Domestic Product (GRDP), absorbs labor, and embody community welfare. Covid-19 pandemic impact on various economic sectors, including agricultural sector in Riau Province. This study aims to analyze: (1) contribution agricultural sector to GRDP before dan during pandemic; (2) labor productivity in agricultural sector before and during pandemic; (3) level of community welfare before and during pandemic. Research method used literature study, secondary data time series in 2016-2021. The data were analyzed by qualitative descriptive and quantitative descriptive analysis. The results showed; (1) contribution of agricultural sector to GRDP before pandemic was 22.89%, during pandemic increased to 25.53%. (2) average labor productivity agricultural sector before pandemic was Rp.143,110,568 per year, increased during pandemic to Rp.168,293,208 per year. (3) community welfare before pandemic of 920.26 kilo equivalent to rice per year with sufficient criteria, meanwhile during pandemic increased to 1,062.06 kilo equivalent to rice per year with decent living criteria.